Implementation of the Rural and Urban Land and Building Tax Incentive Policy (PBB-P2) in Bekasi City in 2024 - Amelia Shalsabila; Inayati Inayati (Economic: Journal Economic and Business, 2025)
The 2024 Rural and Urban Land and Building Tax (PBB-P2) incentive policy in Bekasi City is a strategic step by the local government to improve taxpayer compliance and accelerate the realization of regional revenue. Although in the form of fiscal relief, this incentive is able to encourage tax payments by reducing payment barriers, eliminating administrative sanctions, and stimulating taxpayers who were previously delinquent. Bekasi City's fiscal potential continues to increase along with the expansion of the property sector and increasing land values, thereby strengthening the tax base. This study aims to analyze the implementation of this incentive policy using Edward III's theory, which includes the dimensions of communication, resources, disposition, and bureaucratic structure. The method used is descriptive qualitative through interviews with Bapenda officials, village officials, and taxpayers, as well as analysis of official documents. The results show that the bureaucratic structure and disposition of implementers support successful implementation, but unequal public communication and limited resources hinder the policy's effectiveness. This study emphasizes the importance of strengthening socialization, updating databases, and supporting resources to ensure the continued effectiveness of the PBB-P2 incentive in the era of regional fiscal reform.